"... even if no one sees us ..." An analysis of the perception of street sweepers about their activity and its relationship with the level of satisfaction (Research, Society and Development, 2020)
The purpose of this paper is show how the perception of the employees leads to influence on job satisfaction (Production x Health), stratifying information about human behavior in productivity. The phenomenology of perception proposed by Merleau-Ponty is presented in a way that enables the confrontation of literature ideas with practice in order to analyze and describe the experiences of the individuals in a more concrete way. The research was conducted with employees on a cleaning company in the city of Itabira, Minas Gerais, in order to understand human perception within the business environment. The methods used for research were the Ethnography and the case study, comprising a body immersion in the workplace and identifying some factors that lead the worker dissatisfaction. As a result, the article demonstrates a clear definition of perception in relation with motivation, satisfaction and productivity related to discrimination, occupational health and absenteeism.